Property management, disability awareness and inclusive built environment. Issue 5 (17th October 2016) - Yau, Yung; Lau, Wai Kin
Abstract : Purpose: The purpose of this paper is to investigate the level of disability awareness in the property management industry in Hong Kong. Design/methodology/approach: A structured questionnaire survey was conducted on 342 local property management practitioners. The survey was conducted online in the period between 15 September 2014 and 30 November 2014 to collect various information of the respondents such as their backgrounds, different perceptions towards the disabled and disability awareness. In addition, in-depth interviews with two front-line property management personnel were undertaken to provide a more narrative account of the topic. Findings: The respondents generally recognized the importance of inclusive built environment to persons with disabilities (PWD) and the vital role played by property management in safeguarding the interests of PWD. However, the research found that some misconceptions about disabilities still prevailed in the industry and the interests of PWD have received inadequate consideration in the routine property management tasks performed by the practitioners, reflecting a lack of disability awareness in the local property management industry. Research limitations/implications: The research findings provide a baseline reference for longitudinal tracking of the disability awareness among property management practitioners in the future. Practical implications: Drawing on the research findings, this paper made several recommendations for improving disability awareness in Hong Kong's property management industry. In addition, the research findings can be used for before-and-after analyses when the public authority strives to evaluate the effectiveness of their programmes, training workshops or campaigns of disability awareness promotion in the industry. Originality/value: The importance of property management in the achievement of inclusive built environment has long been ignored in the literature. This study on disability awareness of property management practitioners is very likely the first of its kind in the world.